El nitrógeno en los suelos derivados de cenizas volcánicas del Altiplano de Pasto, Colombia - Molina A, Cruz E.; BLASCO L, M. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
This study presents some aspects of nitrogen fractionation in the volcanic ash soils of the Andean Highland of Pasto, Nariño, southwest of Colombia . In this area the average annual rainfall and temperature are 781 mm and 13°C respectively. The rock types and pyroclastic materials are of andesitic-dacitic composition. The volcanic ash soils studied have adequate amounts of total-N (about 4,000 ppm) and organic-N (95 per cent of total-N). Native fixed-NH4 was found to range from 32.4 to272.6 ppm and, on average, varied from 1.90 to 4.13 per cent of total-N, whilst exchangeable-NH4 values were between 28.0 to 78.0 ppm varying, on average, as a fraction of total-N from 1.40 to 2.43 per cent. Both, the average concentration of native fixed-NH4 and exchangeable-NH3-N ranged from 0.19 to 29.5 ppm. (on average, 0.16 to 0.32 per cent of total-N).